2011
DOI: 10.1258/jtt.2011.110213
|View full text |Cite
|
Sign up to set email alerts
|

Triage and patient satisfaction among callers in Swedish computer-supported telephone advice nursing

Abstract: SummaryWe investigated satisfaction with a Swedish telenursing service, and the healthcare seeking behaviour among callers who received a less urgent level of healthcare than they expected. A postal questionnaire was sent to a random selection of callers (n=273) to Swedish Healthcare Direct in October 2008. The "cases" were 18 callers where the telenurse recommended a lower level of health care than the caller expected and who were not in complete agreement with the nurse. The "controls" were 22 callers who ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 20 publications
2
33
1
Order By: Relevance
“…In a previous study (Rahmqvist et al, 2011), which investigated satisfaction and care-seeking behaviour among callers to this SHD site, a postal questionnaire was sent to a random selection of callers (n=273). Based on this randomized sample a group of callers (n=40) who had received a less urgent level of care than they had expected and/or was not in agreement with the telephone nurses regarding the recommended level were identified, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a previous study (Rahmqvist et al, 2011), which investigated satisfaction and care-seeking behaviour among callers to this SHD site, a postal questionnaire was sent to a random selection of callers (n=273). Based on this randomized sample a group of callers (n=40) who had received a less urgent level of care than they had expected and/or was not in agreement with the telephone nurses regarding the recommended level were identified, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The questionnaire was developed from an existing evaluation of patient satisfaction among callers to the SHD (Rahmqvist et al . ) and a modified version of the Quality from the Patient Perspective (QPP) questionnaire for telephone nursing (http://www.improveit.se). Because of its similarity to already tested instruments, no pilot study was performed.…”
Section: The Studymentioning
confidence: 99%
“…Eight publications described patient satisfaction after the consultation provided by the teleconsultation centers 17,19,25,26,39,4244. Other settings include: the management of same-day appointments;6 the provision of teleconsultation services by physicians outside of specialized telemedicine institutions;19,23,45,46 maritime telemedicine;30 prison medicine;24 and teledermatology services 23.…”
Section: Resultsmentioning
confidence: 99%
“…The timing of instrument administration varied considerably across the studies. In addition, 16 publications (52%) reported the distribution of the questionnaires within 7 days of the consultation,6,1924,27,3234,36,37,4042 seven studies (23%) between 14–28 days,17,18,26,28,38,39,44 and one publication (3%) reported a latency of 4–16 months 30. Also, seven (23%) studies did not report on the timing of the instrument’s administration (Table 1).…”
Section: Resultsmentioning
confidence: 99%